Measurement of MHC/Peptide Interactions by Gel Filtration or Monoclonal Antibody Capture. (1st February 2013) - Sidney, John; Southwood, Scott; Moore, Carrie; Oseroff, Carla; Pinilla, Clemencia; Grey, Howard M.; Sette, Alessandro
Abstract: This unit describes a technique for the direct and quantitative measurement of the capacity of peptide ligands to bind Class I and Class II MHC molecules. The binding of a peptide of interest to MHC is assessed based on its ability to inhibit the binding of a radiolabeled probe peptide to purified MHC molecules. This unit includes protocols for the purification of Class I and Class II MHC molecules by affinity chromatography, and for the radiolabeling of peptides using the chloramine T method. An alternate protocol describes alterations in the basic protocol that are necessary when performing direct binding assays, which are required for (1) selecting appropriate high‐affinity, assay‐specific, radiolabeled ligands, and (2) determining the amount of MHC necessary to yield assays with the highest sensitivity. After a predetermined incubation period, dependent upon the allele under examination, the bound and unbound radiolabeled species are separated, and their relative amounts are determined. Three methods for separation are described, two utilizing size‐exclusion gel‐filtration chromatography and a third using monoclonal antibody capture of MHC. Data analysis for each method is also explained. Curr. Protoc. Immunol . 100:18.3.1‐18.3.36. © 2013 by John Wiley & Sons, Inc.